AEFI Reporting Rates in Albania During 2008-2015: A Retrospective Analysis of AEFI Reporting Forms (European Journal of Interdisciplinary Studies, 2016)
In Albania, passive AEFI surveillance is conducted by Institute of Public Health, which is under the supervision of Ministry of Health. Reports of suspected adverse events following immunisation (AEFI) are reviewed by the Control of infectious disease department in the Institute of Public Health and recorded in a central database. In this study AEFI database is analysed for individual AEFI reporting forms during 2008-2015. AEFI reporting rates and their patterns were assessed. At 2003 a national standardized AEFI reporting form was introduced to the health-care workers who were obligated to report any observed AEFI. This form was changed and added more requisites in 2008 and nowadays this is the formal AEFI reporting form in Albania. Safe vaccines are essential to preserve high adherence to immunization programs¬ [1]. During the last years the reporting rate increased significantly due to implementation of enhanced vaccine safety reporting strategies but it is still low and underreporting remains one of the limits of passive surveillance. Reporting rates were calculated using as a denominator the administered doses of vaccines.